Membrane Targeting of C2GAP1 Enables Dictyostelium discoideum to Sense Chemoattractant Gradient at a Higher Concentration Range - Xu, Xuehua; Bhimani, Smit; Pots, Henderikus; Wen, Xi; Jeon, Taeck J.; Kortholt, Arjan; Jin, Tian (Frontiers in Cell and Developmental Biology, 2021)
Chemotaxis, which is G protein-coupled receptor (GPCR)-mediated directional cell migration, plays pivotal roles in diverse human diseases, including recruitment of leukocytes to inflammation sites and metastasis of cancer. It is still not fully understood how eukaryotes sense and chemotax in response to chemoattractants with an enormous concentration range. A genetically traceable model organism, Dictyostelium discoideum, is the best-studied organism for GPCR-mediated chemotaxis. Recently, we have shown that C2GAP1 controls G protein coupled receptor-mediated Ras adaptation and chemotaxis. Here, we investigated the molecular mechanism and the biological function of C2GAP1 membrane targeting for chemotaxis. We show that calcium and phospholipids on the plasma membrane play critical roles in membrane targeting of C2GAP1. Cells lacking C2GAP1 (c2gapA-) displayed an improved chemotaxis in response to chemoattractant gradients at subsensitive or low concentrations (<100 nM), while exhibiting impaired chemotaxis in response to gradients at high concentrations (>1 micro M). Taken together, our results demonstrate that the membrane targeting of C2GAP1 enables D. discoideum cells to sense chemoattractant gradients at a higher concentration range. This mechanism is likely an evolutionarily conserved molecular mechanism of Ras regulation in the adaptation and chemotaxis of eukaryotes.